2013
DOI: 10.1021/tx400145e
|View full text |Cite
|
Sign up to set email alerts
|

Replication past the Butadiene Diepoxide-Derived DNA Adduct S-[4-(N6-Deoxyadenosinyl)-2,3-dihydroxybutyl]glutathione by DNA Polymerases

Abstract: 1,2,3,4-Diepoxybutane (DEB), a metabolite of the carcinogen butadiene, has been shown to cause glutathione (GSH)-dependent base-substitution mutations, especially A:T to G:C in Salmonella typhimurium TA1535 (Chem. Res. Toxicol. 23, 1544 (2010)) and Escherichia coli TRG8 cells (Chem. Res. Toxicol. 25, 1522 (2012)). We previously identified S-[4-(N6-deoxyadenosinyl)-2,3-dihydroxybutyl]GSH (N6dA-(OH)2butyl-GSH) as a major adduct in the reaction of S-(2-hydroxy-3,4-epoxybutyl)glutathione (DEB-GSH conjugate) with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 51 publications
8
26
0
Order By: Relevance
“…As observed previously for C5-thymine lesions (36), hPol was more efficient than hPol . Higher catalytic efficiency of hPol than hPol is consistent with previous reports for other bulky nucleobase lesions such as exocyclic adducts (35,(71)(72)(73) and DNA-glutathione conjugates (74). Unlike C5-thymine-peptide lesions, which induce high numbers of frameshift and base substitution mutations upon primer extension in the presence of hPol and hPol (36), C7-G conjugated DPCs were not miscoding.…”
supporting
confidence: 90%
“…As observed previously for C5-thymine lesions (36), hPol was more efficient than hPol . Higher catalytic efficiency of hPol than hPol is consistent with previous reports for other bulky nucleobase lesions such as exocyclic adducts (35,(71)(72)(73) and DNA-glutathione conjugates (74). Unlike C5-thymine-peptide lesions, which induce high numbers of frameshift and base substitution mutations upon primer extension in the presence of hPol and hPol (36), C7-G conjugated DPCs were not miscoding.…”
supporting
confidence: 90%
“…Previous investigations have revealed that the ability of DNA polymerases to bypass DNA-peptide conjugates is dependent on the lesion size, the attachment site within the DNA, and polymerase identity (10,(21)(22)(23)(24)(25)(26)(27)(28)(29). Lloyd and co-workers (26) have reported that human polymerase (hpol) and its Escherichia coli orthologue pol IV were able to catalyze error-free primer extension past DNA templates containing tetra-and dodecapeptides conjugated to the N 2 position of guanine via a trimethylene linker.…”
Section: Dna-protein Cross-links (Dpcs)mentioning
confidence: 99%
“…Yamanaka et al (27) proposed that small major groove DPC adducts have sufficient conformational flexibility to be accommodated within the active site of TLS polymerases without disturbing primer-template-enzyme interactions, although the corresponding minor groove adducts block replication. More recently, Guengerich and co-workers (29) reported that human polymerases and , as well as bacterial polymerases pol T7 and DPO4, were capable of replicating DNA containing S- [4-(N 6 -deoxyadenosinyl)-2,3-dihydroxybutyl] glutathione adducts (N 6 -dA-(OH) 2 butyl-GlyCys-␥Glu). However, to our knowledge, no systematic studies have been performed to examine replication bypass of DPCs conjugated to pyrimidine bases on DNA, despite their potential significance in vivo.…”
Section: Dna-protein Cross-links (Dpcs)mentioning
confidence: 99%
See 2 more Smart Citations